Current Topics (The Muslim world, 1933)
Romanticism in Islam and Dante A South African Moslem Conference New Highways in Yemen A New Motor Route in Arabia The Mosques of Peiping Was Mohammed a False Prophet? Islam and Socialism A Versified Koran from Cyprus Islam and Modernist Churchmen Le Film “Christus”à Téhéran Education of Women in Syria Progress in Northern Nigeria The Koran in Chinese Islam in Pittsburgh “We Detest War” The Rev. Percy Smith, B.D. (London)